Sustainable supply chain management practices in retailing : Qualitative content analysis based on sustainability reports - Pekkala, Mikko (My University, 2023)
Sustainable supply chain management has become an important topic in a world where consumers are demanding more and more sustainable products. Sustainable supply chain management has received major attention in both academic research and among businesses. Nevertheless, there are limited amount of research about the topic from the retailer’s perspective. Most of the existing research focuses on the manufacturing industry. Still, the significant role of retailers as an interface between the manufacturers and consumers offers attractive basis for studying retailers sustainable supply chain management. The objective of this master’s thesis is to figure out how the Finnish listed retailers are fostering sustainable supply chain management by using sustainable development as the dominant framework, and how the selected case companies are disclosing it as part of their sustainability reporting. In addition to this, case companies’ commitments towards sustainable development goals are researched as well. This research is conducted as a qualitative content analysis where case companies’ sustainability reports are analyzed from the years 2020-2022. The key research findings indicates that the selected retailers largely do have similar practices to verify sustainability of their supply chains. Among these practices, companies own operational principles and audits play a significant role in verifying supply chain sustainability. The observed practices were more reactive in nature, and the sustainability reports provided rather variable evidence of more proactive practices. However, companies utilizing GRI reporting disclosed more comprehensively and transparently proactive practices. The research findings also exposed that only two out of the four case companies have adopted the United Nations Sustainable Development Goals and integrated them into their sustainability reporting. This research studies the key practices adopted by Finnish retailers to ensure the sustainability of their supply chains and how these are disclosed as part of sustainability reporting. In addition to this, this research provides insights into sustainable supply chain management in the retail sector and how companies contribute towards the United Nations Sustainable Development Goals.

Kestävä toimitusketjujen hallinta on noussut yhä tärkeämmäksi tekijäksi maailmassa, jossa kuluttajat vaativat yhä enemmän kestävän kehityksen mukaisia tuotteita. Kestävä toimitusketjujen hallinta on saanut paljon huomiota niin akateemisissa tutkimuksissa, kuin yritystenkin keskuudessa. Tästä huolimatta aihetta on tutkittu rajallisesti vähittäiskaupan näkökulmasta. Valtaosa tutkimuksista käsittelee valmistavaa teollisuutta, mutta vähittäiskauppojen merkittävä rooli valmistavan teollisuuden ja kuluttajien rajapinnassa tarjoaa otollisen lähtökohdan tutkia vähittäiskauppiaiden kestävää toimitusketjujen hallintaa. Tämän Pro Gradu -tutkielman tavoitteena on selvittää kuinka listatut suomalaiset vähittäiskauppiaat edistävät kestävää toimitusketjujen hallintaa kestävän kehityksen näkökulmasta, ja kuinka yritykset raportoivat tästä osana vastuullisuusraporttejaan. Tämän lisäksi tutkitaan kuinka valitut vähittäiskauppiaat ovat sitoutuneet YK:n kestävän kehityksen tavoitteisiin osana toimintaansa. Tutkimus toteutettiin käyttämällä laadullista sisällönanalyysiä, jonka avulla tutkittiin valittujen yritysten vastuullisuusraportteja vuosilta 2020–2022. Keskeiset tutkimustulokset osoittavat, että valituilla vähittäiskauppiailla on pitkälti käytössä samankaltaisia keinoja toimitusketjujen kestävyyden varmistamiseksi. Näistä erityisesti yritysten omat toimintaperiaatteet ja auditoinnit ovat merkittävässä roolissa toimitusketjun kestävyyden varmistamiseksi. Havaitut keinot olivat enimmäkseen reaktiivisia ja vastuullisuusraportit tarjosivat vaihtelevasti näyttöä proaktiivisista toimista, kuten aktiivisesta toimittajayhteistyöstä. Toisaalta GRI-raportointia käyttäneet yritykset julkaisivat kattavammin ja läpinäkyvämmin myös proaktiivisia toimia. Tutkimustuloksista paljastui myös, että vain kaksi neljästä valitusta vähittäiskauppiaasta olivat ottaneet käyttöönsä YK:n kestävän kehityksen tavoitteet, ja integroineet nämä osaksi raportointiaan. Tämä tutkimus selvittää suomalaisten vähittäiskauppiaiden keskeisiä menetelmiä toimitusketjujen kestävyyden varmistamiseksi, sekä kuinka valitut yritykset raportoivat tätä osana vastuullisuusraportointiaan. Tämän lisäksi tutkimus tarjoaa ymmärrystä vähittäiskaupan kestävästä toimitusketjun hallinnasta, sekä kuinka yritykset myötävaikuttavat YK:n kestävän kehityksen tavoitteisiin.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management